Cover Picture: New Insights into Structural Evolution of LiNiO2 Revealed by Operando Neutron Diffraction (Batteries & Supercaps 11/2021). Issue 11 (18th October 2021) - Chien, Po‐Hsiu; Wu, Xianyang; Song, Bohang; Yang, Zhijie; Waters, Crystal K.; Everett, Michelle S.; Lin, Feng; Du, Zhijia; Liu, Jue
Abstract : The Front Cover shows the operando neutron diffraction study of structural evolution of LiNiO2 cathode in a jelly‐type full cell. The anomalous increase of Ni−O bond length at high degrees of charge is successfully captured, bringing new insights into the structure and electronic structure evolution of LiNiO2 at deep charging states. More information can be found in the Article by Z. Du, J. Liu and co‐workers .